Self-cleaning filter is key for Helsinki project. Issue 6 (November 2016) - Unknown
Abstract : Atunneling wastewater project in Helsinki, Finland, found that its settling tanks did not provide sufficient total suspended solids reduction. In addition, the use of coagulants and flocculants to aid settling was not working, so a Finnish company was brought in and used a self-cleaning filter to solve the problem.